Preparation, characterization and kinetic evaluation of struvite in various carboxylic acids - SAYAN, PERVİZ; POLAT, SEVGİ (ELSEVIER, 2020)
In this study, struvite crystallization was investigated using different carboxylic acid media-propionic, tartaric, and trimesic acid. The struvite was synthesized as a result of the reaction between magnesium chloride hexahydrate and ammonium dihydrogen phosphate. In the first part. of the study, the crystals prepared with and without additives were characterized through X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and zeta potential measurements. XRD results showed that the struvite prepared in pure media comprised crystals with the normal orthorhombic structure. SEM images confirmed that the struvite underwent morphological changes when prepared in carboxylic acid media. FTIR analysis indicated that the carboxylic acids affected the functional groups of the struvite. Zeta potential measurements showed that struvite crystals have a -13.2 +/- 1.8 mV zeta potential value, and that the surface of the crystals in trimesic acid media became more positive than that created in pure media with an increase in value to -2.3 +/- 0.9 mV. In the second part of the study, the thermal decomposition of the struvite crystals was investigated in detail. The thermal data were used to calculate the activation energy that corresponded to struvite dehydration prepared with and without additives using a nonisothermal kinetic analysis based on the Flynn-Wall-Ozawa, Kissinger-Akahira-Sunose, Starink, and Tang models. The mean activation energy calculated for struvite crystallization in pure media was between 56.06 and 52.13 kJ/mol, depending on the kinetic method used.
Keywords: Struvite; Crystallization; Morphology; Carboxylic Acids; Kinetics; Model free; ACTIVATION-ENERGIES; PHOSPHORUS RECOVERY; PROCESS PARAMETERS; CITRIC-ACID; PILOT-SCALE; CRYSTALLIZATION; PRECIPITATION; MORPHOLOGY; WASTE; DECOMPOSITION